METAFORA DALAM LIRIK LAGU JOHNNY CASH (SUATU ANALISIS SEMANTIK) - MANE, SRIWAHYUNI S. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Metaphor is part of figurative languange that compares one thing to another. Metaphor helps speakers or writers to describe about two different things. Metaphor is not only found in a poem but also in a song.This study entitled â€œMethapor in The Song Lyrics By Johnny Cash (A Semantic Analysis)â€ is an attempt to identify kinds of metaphor and to analyze the meaning of metaphor in the song lyrics. The method used in this research is descriptive method. In collecting the data, the writer uses theory of Lakoff and Johnson (1980) about metaphor conseptual theory to identify kinds of metaphor. Then the writer analized the meaning to determine target and source based on theory of Lakoff and Johnson (1980). The results of this study show that there are 15 phrases containing structural metaphor, 12 phrases containing orientational metaphor and 17 phrases containing Ontological metaphor. The meaning of each lyrics are various. Every word is transfered from abstract to concrete meaning and each lyric refers to certain object of target and source. Â Keywords: Metaphoric Meaning, Songs By Johnny Cash, Semantic Analysis